2022
DOI: 10.1093/geront/gnac147
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Address COVID-19 Vaccine Hesitancy Among Ohio Nursing Home Staff

Abstract: Background and Objectives Despite federal legislation requiring nursing home (NH) staff members to be vaccinated against COVID-19, unvaccinated staff pose an ongoing public health risk. The research question guiding this study is as follows: What is the relationship between strategies to address vaccine hesitancy and vaccination rates among staff? We used the Diffusion of Innovation (DOI) theory as a theoretical framework. Research Design and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Since social influence can propagate vaccine hesitancy within clusters [52], and the acts of others are an important reference for decision making in a congregate environment [53], targeted inventions should be tailored for RCHEs. Echoing our findings that emotional loneliness predicted vaccine hesitancy among staff, overseas counterparts considered "having someone like themselves vaccinated" to be motivating [23], and peer counseling was a significant strategy in boosting the uptake rate among staff [54].…”
Section: Results Implicationsmentioning
confidence: 69%
“…Since social influence can propagate vaccine hesitancy within clusters [52], and the acts of others are an important reference for decision making in a congregate environment [53], targeted inventions should be tailored for RCHEs. Echoing our findings that emotional loneliness predicted vaccine hesitancy among staff, overseas counterparts considered "having someone like themselves vaccinated" to be motivating [23], and peer counseling was a significant strategy in boosting the uptake rate among staff [54].…”
Section: Results Implicationsmentioning
confidence: 69%
“…Another qualitative study indicated that peer-positive experiences may also be effective to address vaccine hesitancy [35] . A recent study found that strategies such as a peer counseling and providing sick leave or time off for vaccine symptoms could be effective to increase vaccination rates among NHS in Ohio, USA [44] .…”
Section: Discussionmentioning
confidence: 99%